Dissecting the Roles of Phosphorus Use Efficiency, Organic Acid Anions, and Aluminum-Responsive Genes under Aluminum Toxicity and Phosphorus Deficiency in Ryegrass Plants - Leyla Parra-Almuna; Sofía Pontigo; Antonieta Ruiz; Felipe González; Nuria Ferrol; María de la Luz Mora; Paula Cartes (Plants, 2024)
Aluminum (Al) toxicity and phosphorus (P) deficiency are widely recognized as major constraints to agricultural productivity in acidic soils. Under this scenario, the development of ryegrass plants with enhanced P use efficiency and Al resistance is a promising approach by which to maintain pasture production. In this study, we assessed the contribution of growth traits, P efficiency, organic acid anion (OA) exudation, and the expression of Al-responsive genes in improving tolerance to concurrent low-P and Al stress in ryegrass (Lolium perenne L.). Ryegrass plants were hydroponically grown under optimal (0.1 mM) or low-P (0.01 mM) conditions for 21 days, and further supplied with Al (0 and 0.2 mM) for 3 h, 24 h and 7 days. Accordingly, higher Al accumulation in the roots and lower Al translocation to the shoots were found in ryegrass exposed to both stresses. Aluminum toxicity and P limitation did not change the OA exudation pattern exhibited by roots. However, an improvement in the root growth traits and P accumulation was found, suggesting an enhancement in Al tolerance and P efficiency under combined Al and low-P stress. Al-responsive genes were highly upregulated by Al stress and P limitation, and also closely related to P utilization efficiency. Overall, our results provide evidence of the specific strategies used by ryegrass to co-adapt to multiple stresses in acid soils.